Applying the resource dependence theory to enhance supply chain management of small and medium scale enterprises (SMEs) in the context of COVID-19 / Praveen M Kulkarni, Gurudutt Nayak and Arun Kumar P - M Kulkarni, Praveen; Nayak, Gurudutt; P, Arun Kumar (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The Covid-19 pandemic had deeply affected supply chain management across industries, necessitating firms to redefine their strategies to reduce the risk and imbalance caused by the disruption. The study highlights how external risk factors have influenced the internal and organizational factors of the small and medium enterprises (SMEs) in dealing with their supply chain disruptions. We applied the resource dependence theory to illustrate this aspect and also to understand the factors that impact supply chain management. The study applied the interpretive structural modelling (ISM) methodology and Cross Impact Matrix Multiplication Applied to Classification (MICMAC) methodology to understand the inter-dependence relationship between these factors of risk in supply chain management during Covid-19. Our study was specific to the ongoing COVID 19 pandemic as the external factor disrupting supply chains and impacting a firm’s internal and organizational factors in dealing with the impact. Our results showed that external factors deeply influence the internal factors governing supply chain management, which in turn, impact firm performance.